Kajian Literature : Pengaruh Etika Bisnis Terhadap Kepercayaan Dan Kepuasan Konsumen - Atika Fitriani; Hasibuan, Sarifah; Wijaya, Melki; Agustiawan Agustiawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
In the context of doing business and interacting with others, ethics plays a crucial role. Business ethics is not just an element, but a determinant of the success of a business. This study aims to investigate and analyze the role of Business Ethics in building consumer trust and satisfaction. The research method applied is Systematic Literature Review (SLR) with a focus on journals that have been published from 2014 to 2023. The results of this study, namely: 1. Business ethics has a positive effect on consumer trust, 2. Business ethics has a positive effect on customer satisfaction.